2010
DOI: 10.4314/gmj.v40i3.55262
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine retained fetal bones as a cause of secondary infertility

Abstract: SUMMARYThree cases of retained fetal bones, the first two after mid-trimester termination of pregnancy and the third after dilatation and evacuation (D&E) of the uterus for a missed abortion, are presented. All the cases were complicated by secondary infertility. In all the cases the diagnosis was confirmed by a high resolution pelvic ultrasound scan. The pieces of bones were removed at dilatation and evacuation under general anaesthesia. In two of the cases pregnancy occurred within 6 months of removal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A rare but significant cause of uterine factor of infertility is retained fetal bones from previous mid-trimester D and E. Apart from secondary infertility, retained fetal bones may also present with irregular bleeding per vaginum, dysmenorrhea, dysparauneia and chronic pelvic pain. 3 Verma et al reported the case of a 20 year old woman with history of multiple terminations of pregnancy leading to chronic pelvic pain which got relieved after hysteroscopic removal of the intrauterine fetal bone. 4 Gupta N et al reported a case of 35-year-old woman with history of lower abdominal pain and amenorrhea for 2 months following a surgical second trimester abortion.…”
Section: Discussionmentioning
confidence: 99%
“…A rare but significant cause of uterine factor of infertility is retained fetal bones from previous mid-trimester D and E. Apart from secondary infertility, retained fetal bones may also present with irregular bleeding per vaginum, dysmenorrhea, dysparauneia and chronic pelvic pain. 3 Verma et al reported the case of a 20 year old woman with history of multiple terminations of pregnancy leading to chronic pelvic pain which got relieved after hysteroscopic removal of the intrauterine fetal bone. 4 Gupta N et al reported a case of 35-year-old woman with history of lower abdominal pain and amenorrhea for 2 months following a surgical second trimester abortion.…”
Section: Discussionmentioning
confidence: 99%
“…In the English literature, during 1994 and 2014, there are 21 reports evaluating the conception performance of 64 women presenting with osseous metaplasia [1,2,8,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29] (table 1). According to the demographic features of the given patients in table 1, 60 of 64 women (93.8%) experienced at least one miscarriage or medical termination.…”
Section: Discussionmentioning
confidence: 99%
“…Many theories have been proposed to explain the origin, such as continuous and strong endometrial estrogenic stimulation, dystrophic calcification of retained and necrotic tissues, metastatic calcification, metabolic disorders and hypercalcemia (hypervitaminosis D or hyperphosphatemia). [7][8][9] Direct implantation of retained fetal bones was proposed by some authors, 10 but this might be valid for second-trimester abortions. However, there are also rare case reports of nulliparous patients or of abortion that occurred at a very early gestational age, when no fetal bony tissue had yet been formed.…”
Section: Discussionmentioning
confidence: 99%